Survey of Arboreal gastropods in mangrove ecosystem of Bagonbanua and Canigaran Islet, Guiuan, Eastern Samar - Lucero, Aylla Mae T. author; Dela Cruz, Margarita (Tacloban City Aylla Mae T. Lucero, 2014)
Mangrove ecosystems harbour a diversity of terrestrial and marine fauna. Abundance, diversity and identification of arboreal gastropods were obtained in this study. The study was carried out in the mangrove ecosystem of Bagonbanua and Canigaran, surveyed from February to April 2014. Survey was conducted on three 1x1 m square transects within a 10x10 meter square plot. A total of 560 individuals of gastropods were found belonging to the five families of Littorinidae, Neritidae, Potamididae, Mitridae and Trochidae. Results showed that L. scabra has the highest species abundance and density. Diversity values were found to be higher in Bagonbanua than Canigaran, however t-test revealed that there is no significant difference between the values across sites.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.